Freshwater ecoregions of Africa and Madagascar : a conservation assessment - Thieme, Michele L. (Island Press, 2005)
Essay 5.1: Safeguarding Human Health, Safeguarding Aquatic Snail Diversity: Conflicting Goals? -- Ch. 6: Africa's Freshwater Systems and Their Future -- Who's Watching the Water -- Conservation Planning in Ecoregions and River Basins -- Visionary Work in Freshwater Ecoregions and River Basins -- Challenges to Freshwater Conservation and Sustainable Development in Africa and Madagascar -- Essay 6.1: The Convention on Wetlands (Ramsar): An International Treaty Sparks Freshwater Conservation -- Essay 6.2: Lake Naivasha, Kenya: Community Management of a Ramsar Site.